Hedges Analysis in British Council Teacher Podcast: How Can I Use Different Languages in My Teaching? - Juwantoro, Ario; Setyawan, Agustinus Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research looked into how hedges were used in the British Council Teacher Podcast. How can I use different languages in my teaching? This research set out to 1) characterize the language characteristics of hedges and 2) examine the roles that hedges play in conversation. Because this study aims to provide explanations, the qualitative method is employed. The data consisted of utterances made by the podcast participants—Chris, Sue, Mei, and Tony—that indicated the use of hedges. Through the examination of 40 hedging instances, the research identified various types of hedges, with modal lexical verbs being the most frequently used (20%), followed by approximators, introduction phrases, and adjectival/adverbial modal phrases (each at 17.5%).